PEMBINAAN DIVERSIFIKASI PRODUK DALAM PENJUALAN UMKM DI DESA SUMBER REJO KABUPATEN BATUBARA - Rosmita Sari Siregar; Jholant Bringg Luck Amelia Sinaga; Jessy Safitri Sitorus; Wirda Lilia; Mesrawati, Mesrawati; Antonius Simbolon (Yayasan Nusantara Hasana Berdikari, 2025)
The background of this activity is the challenges faced by UMKM in facing digital transformation and increasingly competitive market competition. The team identified that the majority of UMKM still use conventional marketing methods and have limited understanding of digital technology. The methodology used includes several important stages. First, socialization is carried out on the importance of digital marketing in business development. Then, participants are given practical training covering the use of social media, creating interesting content, online marketing strategies, and digital platform management. Each session is designed interactively, allowing participants to directly practice the new skills they have learned. In its implementation, the community service team provides intensive assistance to each UMKM actor. The results achieved are very significant. UMKM actors have increased their understanding and skills in managing their business digitally.